PENGEMBANGAN SISTEM DATA WAREHOUSE DAN WEB API UNTUK DUKUNGAN PENGAMBILAN KEPUTUSAN PRODUKSI BUAH DI SULAWESI SELATAN - Ismi Batari Agung; Agustinus Rioland; Dewantara, Amhar Davi; Rini Nur (Journal of Informatics and Computer Engineering Research, 2025)
South Sulawesi possesses significant potential in the horticultural sector, particularly for leading fruit commodities such as jackfruit, mango, and duku, capable of meeting both domestic and international market demands. However, the scattered nature ofproduction data across various districts hinders effective analysis and strategic decision-making. This project develops an integrated system, comprising a data warehouse and a Web API, to present fruit production data systematically, structurally, and accessibly. The data warehouse is designed using a star schema, with a fruit production fact table that includes calculations like dominance percentages and annual growth. Dimension tables consist of time, location, fruit type, and sub-district, all supporting in-depth analysis. A Web API is developed to provide real-time and standardized access to analysis results. This system is expected to support data-driven decision-making for government agencies, researchers, and horticultural industry players in optimizing the sector's potential.